2022
DOI: 10.1101/2022.05.30.22275753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and superior immunogenicity of heterologous boosting with an RBD-based SARS-CoV-2 mRNA vaccine in Chinese adults

Abstract: Homologous and heterologous booster with COVID-19 mRNA vaccines represent the most effective strategy to prevent the ongoing Omicron pandemic. The additional protection from these prototype SARS-CoV-2 S-targeting vaccine was attributed to the increased RBD-specific memory B cells with expanded potency and breadth. Herein, we show the safety and immunogenicity of heterologous boosting with the RBD-targeting mRNA vaccine AWcorna (also term ARCoV) in Chinese adults who have received two doses inactivated vaccine.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recent studies revealed that the heterologous boost strategy could enhance the background neutralization ability induced by the prototype strain vaccine (47)(48)(49). However, this strategy was not fully effective against Omicron subvariant infection (50).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that the heterologous boost strategy could enhance the background neutralization ability induced by the prototype strain vaccine (47)(48)(49). However, this strategy was not fully effective against Omicron subvariant infection (50).…”
Section: Discussionmentioning
confidence: 99%
“…In reverse, heterologous boosting with Ad26.COV2.S after BNT162b2 prime vaccination can also induce durable humoral and cellular immune responses 72 . An inactivated vaccine plus a recombinant adenovirus vectored vaccine or a recombinant protein subunit vaccine or a mRNA vaccine are additional heterologous vaccine regimens [73][74][75][76][77] . For example, initial vaccination with two doses of CoronaVac followed by heterologous boosting with the Ad5-nCoV induced significantly higher neutralizing antibody levels against the index virus and the Delta variant than did homologous boosting (5.9-fold and 6.7-fold, respectively) 73 .…”
Section: Heterologous Prime-boost Regimensmentioning
confidence: 99%